Sosialisasi Optimalisasi UMKM melalui Digitalisasi Agribisnis, K3, Perlindungan Paten, dan Sistem Pembukuan di Desa Pugeran Kec. Gondang Mojokerto - Mochamad Irfan; Rizka Amelia Rachamadita; Aditya Wardhana; Mochammad Dzulfiqar Khoirumansyah; Nova Belinda Ramadhani; Fella Amelia Kartikasari; Alym Wiranda Khofsoh; Purwanti Agustin; Nur Cita Amalia; Dewi Agustia Ningsih; Maya Rosita; Eka Hartalina; Perdana Faishal Abdillah; Muhammad Zaenal Adiroso; Muhammad Reza Syahputra; Muhammad Rafli Al Hafits; Reza Saifudin Falah; Afrian Nugraha Wijaya; Fauzan Rahmat Abdillah; Yudik Prasetiawan; Kholifah Widya Ashari; Bagas Taruna; Rahmat Arwin Wicaksono; Samuel Yudea (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
The purpose of this community service program is to enhance the capacity and independence of Micro, Small, and Medium Enterprises (MSMEs) by providing improved training in business management. The program covers the use of digital technology in the agricultural sector, the implementation of occupational safety and health practices, intellectual property protection, and simple financial record-keeping practices. In Pugeran Village, the activities were carried out using a collaborative approach involving the village government, MSME actors, and university students participating in the Community Service Program (Kuliah Kerja Nyata). A qualitative descriptive approach was employed through observation, interviews, and focus group discussions, complemented by direct mentoring and counseling sessions. The results indicate that MSME actors have begun to understand the importance of maintaining simple financial records, utilizing digital technology to market their products, and becoming more aware of workplace safety as well as legal protection for their businesses. The program also encouraged MSME actors to shift their perspectives and manage their enterprises in a more professional manner. However, the speed of implementation varied depending on differences in age, educational background, and established business habits. Overall, this community service activity contributed to strengthening the capacity of MSMEs and supporting sustainable economic growth in the village